2018
DOI: 10.1146/annurev-anchem-061417-125956
|View full text |Cite
|
Sign up to set email alerts
|

Wearable and Implantable Sensors for Biomedical Applications

Abstract: Mobile health technologies offer great promise for reducing healthcare costs and improving patient care. Wearable and implantable technologies are contributing to a transformation in the mobile health era in terms of improving healthcare and health outcomes and providing real-time guidance on improved health management and tracking. In this article, we review the biomedical applications of wearable and implantable medical devices and sensors, ranging from monitoring to prevention of diseases, as well as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
120
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(128 citation statements)
references
References 61 publications
1
120
0
Order By: Relevance
“…Other groups are developing ingestible biosensors (a device that can measure chemical substances) . A thorough review of sensors has been reported elsewhere …”
Section: Future Directionsmentioning
confidence: 99%
“…Other groups are developing ingestible biosensors (a device that can measure chemical substances) . A thorough review of sensors has been reported elsewhere …”
Section: Future Directionsmentioning
confidence: 99%
“…Thus, the challenges and prospects have been reviewed recently and are frequently cited [32]. Biomedical applications are provided for wearable and implantable sensors [33]. Even the never-ending story of glucose sensors is reviewed with regard to wearable non-invasive epidermal glucose sensors [34].…”
Section: Highlights Of Research In Analytical Chemistry -2018mentioning
confidence: 99%
“…Traditional medical devices designed to be implanted in the human body to treat either acute or chronic diseases (e.g., cardiac pacemakers, cochlear implants, coronary stents, articular prostheses) are made of (or coated with) inert biocompatible materials and optimized to warrant the organ functionality from days to years, depending of the targeted problem/disease, before surgical retrieval/replacement (when needed) . While for some specific cases (e.g., heart stimulation, hearing loss, coronary heart disease) implanted devices ideally working/operating over the whole patient life are required, in many other cases (e.g., muscle stimulation, bone growth stimulation, neuro stimulation, wound healing) the devices are required to work/operate only for a prescribed amount of time, so that surgical retrieval is eventually needed, which could be potentially dangerous for patient health …”
Section: Introductionmentioning
confidence: 99%